Republic of Mozambique : Staff Report for the Third Review Under the Policy Support Instrument and Request for Modification of Assessment Criteria: Staff Report; Supplement; and Press Release. (IMF Staff Country Reports; Country Report ;, 2011)
The Executive Board of the IMF has completed the third review under the three-year Policy Support Instrument (PSI) for the Republic of Mozambique. Mozambique continues to weather the global economic turmoil well. Real GDP growth is projected to remain above 7 percent in 2011, benefiting from good harvests, a robust performance in the services sector, and the coming online of new megaprojects in the natural resource sector. The authorities' economic program under the PSI will continue to emphasize preserving macroeconomic stability and debt sustainability while promoting economic and social development.